The Implementation of Double Brain Power Strategy to Increase Expository Reading Comprehension - Muhamad Sofian Hadi; Aswir Aswir; Syahr Banu (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Abstract: Purpose - The purpose of this research is to know how much the influence of Double Brain Power Strategy to improve reading comprehension of exposition text students. Design/methodology/approach - This study used quantitative method by using a pre-experimental design. This research will use a pre-experimental design which is the researchers only apply one class as the sample to consecrate pre-test, treatment of behaviour towards and post-test. The researchers also used 1 group pre-test until post-test group design to calculate students' reading before and after treatment. Findings/result - Double Brain Power strategy could increase students’ reading comprehension and give an upgrade to the students in learning reading mastery. Originality/value - Comprehension is the important part when reading to get meaning and information from the texts. Paper type - Research Paper